PROSEDUR ATAS PERJALANAN DINAS PADA DEPUTI PERLINDUNGAN HAK PEREMPUAN KEMENTERIAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK - Dhimas Putri Ayu (2023)
Official Travel is a trip outside the place of origin carried out within the territory of the Republic of Indonesia for the benefit of the state. Official travel is important for the Deputy for the Protection of Women's Rights of the Ministry of Women's Empowerment and Child Protection, because official travel is closely related to the implementation of tasks. This writing aims to find out in more detail about the procedures for official travel from the administration stage to the accountability reporting stage and to find out the amount of costs and documents used in official travel procedures at the Deputy for the Protection of Women's Rights of the Ministry of Women's Empowerment and Child Protection. In this writing, some data and information obtained at the data collection stage through the observation, interview and documentation stages are then processed through a qualitative descriptive analysis method. Based on the discussion of official travel procedures at the Deputy for the Protection of Women's Rights has been running very well and effectively and efficiently because it also uses technological aids in the form of simperjadin applications and is in accordance with applicable laws and regulations.